Prioritizing Zoonoses for Global Health Capacity Building—Themes from One Health Zoonotic Disease Workshops in 7 Countries, 2014–2016 - Stephanie J. Salyer; Rachel Silver; Kerri Simone; Casey Barton Behravesh (Emerging Infectious Diseases, 2017)
Zoonotic diseases represent critical threats to global health security. Effective mitigation of the impact of endemic and emerging zoonotic diseases of public health importance requires multisectoral collaboration and interdisciplinary partnerships. The US Centers for Disease Control and Prevention created the One Health Zoonotic Disease Prioritization Tool to help countries identify zoonotic diseases of greatest national concern using input from representatives of human health, agriculture, environment, and wildlife sectors. We review 7 One Health Zoonotic Disease Prioritization Tool workshops conducted during 2014–2016, highlighting workshop outcomes, lessons learned, and shared themes from countries implementing this process. We also describe the tool’s ability to help countries focus One Health capacity-building efforts to appropriately prevent, detect, and respond to zoonotic disease threats.